PENGARUH OVERKAPASITAS TERHADAP PROFITABILITAS PERUSAHAAN SEKTOR SEMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Abdullah, Abrar Rayhan; Sabarudin, Sabarudin; Bustang, Bustang (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the effect of Overcapacity on the Profitability of Cement Sector Companies listed on the Indonesia Stock Exchange (IDX) in 2018-2023. This study uses a quantitative approach. The data used are secondary data in the form of financial reports of cement sector companies listed on the Indonesia Stock Exchange for the period 2018-2023. Data analysis techniques involve simple linear regression analysis, multiple linear regression analysis and path analysis using SPSS V23.The results of this study indicate that Overcapacity has a significant negative effect on Operational Efficiency, with each one-unit increase in overcapacity causing a decrease in Operational Efficiency of 0.407. In addition, Operational Efficiency is proven to have a positive and significant effect on profitability, with a significance value below 0.05. This study also found that Overcapacity has an indirect negative effect on Profitability through Operational Efficiency. Keywords: Overcapacity, Operational Efficiency, Profitability.